Bundle program of treatment for acute severe type high altitude disease - Zhang, Xue-feng (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2012)
OBJECTIVE: To discuss Bundle treatment of the acute severe type high altitude disease